Inflammatory biomarker pentraxin 3 (PTX3) in relation to obesity, body fat depots and weight loss. (25th January 2014) - Witasp, Anna; Carrero, Juan Jesús; Michaëlsson, Karl; Ahlström, Håkan; Kullberg, Joel; Adamsson, Viola; Risérus, Ulf; Larsson, Anders; Helmersson‐Karlqvist, Johanna; Lind, Lars; Stenvinkel, Peter; Ärnlöv, Johan
<x xml:space="preserve">Abstract</x> Objective The relation between inflammatory markers, adiposity and disease is under extensive study. Here we tested the hypothesis that the immunomodulatory protein pentraxin 3 (PTX3) is associated with adiposity in the general population. Methods Serum PTX3 concentrations, body mass index (BMI), waist circumference (WC) and fat depots, as quantified by dual‐energy X‐ray absorptiometry and magnetic resonance imaging, were assessed in three community‐based cohorts: ULSAM, n = 790, mean age 78 years; PIVUS, n = 1003, mean age 70 years, women 50%; and the NORDIET‐trial, n = 86, mean age 53 years, women 63%. Participants were re‐examined after 5 years (PIVUS, n = 804) or following a 6‐week randomized controlled dietary intervention (NORDIET). Results PTX3 levels were inversely associated with BMI and WC as well as with total and visceral fat (P < 0.05 for all; adjusted for age, inflammatory biomarkers and cardiovascular risk factors). The association between PTX3 and BMI appeared even stronger in nonobese individuals. A decrease in BMI over 5 years as well as weight loss following the NORDIET intervention were associated with increased serum PTX3 concentrations (P < 0.001). Conclusions These consistent data support an inverse association between circulating PTX3 and anthropometrical measures, calling for further mechanistic studies of the link between PTX3 and fat.